Religiosity and Entrepreneurial Intention - Buddi Wibowo (ETIKONOMI, 2017)
Religion and economic activities relationship is an evolving research topic in economics. Secular world-view usually put a side religiosity as just one of non-economic factors. However, religiosity is an important individual characteristic that has significant influence in shaping daily life decisions. Entrepreneurial intentions among undergraduates students need deeper study in order to reveal entrepreneurial intention formation model, intention determinant variables, how those variables interact each other, and how individual religiosity affect intention formation process and intention strength level. Based on Structural Equation Model, personal attitudes and social norms are the most important variables influencing entrepreneurial intentions, besides perceived behavioral control. These three variables are the most important entrepreneurial intentions determinant variable that direcly are influenced by personal beliefs about these factors. Religiosity plays an important role in entrepreneurial intention. Empirical test show that religious student group has stronger personal attitude towards entrepreneurial activity dan perceived behavior control compared to irreligious group.DOI: 10.15408/etk.v16i2.4963